Homocystinuria masquerading as vitamin B12 deficiency - Wadhwani, M; Beri, S; Saili, A; Garg, S (Nepalese Journal of Ophthalmology, 2012)
Background: Homocystinuria is a rare metabolic disorder charcterised by excess homocysteine in the urine. Vitamin B12 deficiency has diverse cutaneous, nervous and ophthalmic manifestations. Objective: To report a case of homocystinuria masquerading as vitamin B 12 deficiency. Case: We hereby are presenting an interesting case of a 4 year old boy who was being treated for Vitamin B 12 deficiency on the basis of history of delayed milestone, abdominal pain and hyperpigmentation of skin which was diagnosed as homocystinuria. Conclusion: It is important to carry out ophthalmological examination in every case of megaloblastic anemia if associated with blurring of vision and mental retardation.DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6554 Nepal J Ophthalmol 2012; 4 (8): 326-328